UJI BAKTERIOLOGIS AIR SUMUR PEMUKIMAN PENDUDUK DI SEKITAR TEMPAT PEMBUANGAN AKHIR SAMPAH - Irdawati, Irdawati; Fifendy, Mades; Kurniati, Deni (IAIN Batusangkar, 2012)
The purpose of this study was to determine the quality of well water in residential areas around the landfill of trash (TPA), Balai Gadang Aia Dingin, Padang, viewed from bacteriological aspects. This study was conducted from March to April 2012 in the Laboratory of Microbiology Department of Biology, Science Faculty, Padang State University (UNP). Samples were taken using Proposive sampling method with 10 wells that are encountered by the first well of the landfill to the distance between 0-100 meters. This study uses Most Probable Number (MPN) using a two-stage testing is Presumtive Test and Confirmative Test with a combination of 3:3:3. can be concluded that the quality of well water residential areas around the landfill 90% did not meet the standards set by the Ministry of Health (KEPMENKES) No. RI. 492/MenKes/PER/IV/2010. Key words : TPA Aia Dingin Padang, bacterial aspects, quality of well water